La cançon occitana de las annadas 80 : darrièr badalh o buf novèl ? - Eric Fraj (Lengas)
During a preparatory seminar to the agrégation langues de France, jointly organised by the universities of Paul Valéry-Montpellier 3 and Toulouse 2 Jean-Jaurès, on 27 March 2021, Eric Fraj, singer and researcher, revisited the question of the Occitan song during the 70s and 80s. Here is the text of his communication, both a testimony and an analysis of this particular moment.